TEENAGER IMAGE IN “TREASURE ISLAND” BY ROBERT LOUIS STEVENSON (Scientific journal of the Fergana State University, 2025)
This article examines the image of teenagers in Treasure Island by Robert Louis Stevenson, focusing on the protagonist, Jim Hawkins. As an archetype of youthful adventure, Jim embodies the universal traits of curiosity, bravery, and moral growth. Using mixed-methods research, the study analyzes textual evidence to highlight Stevenson's portrayal of adolescence within the Victorian socio-cultural framework. The findings reveal that Jim’s character reflects the complexities of teenage identity, balancing youthful impulsiveness with emerging responsibility. Through quantitative coding of thematic elements and qualitative narrative analysis, this study situates Treasure Island as a foundational text in the literary representation of adolescence. The discussion addresses the relevance of these findings for understanding Victorian ideals and their influence on modern teenage portrayals in literature.